Economic reactivation of the merchants of the Riobamba markets during the health emergency. - Moyano Vallejo, Hernán Patricio (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
At present the merchants of the markets have been affected by a worrying economic crisis on which unpredictable consequences are still warned, while the gates are closed in the markets the sales move to the streets in an uncontrollable way. There is no doubt that in the face of the economic emergency facing the country, the diffusion of products, benefits and attractions has also weakened and thereby affecting the sense of belonging in officials and merchants. Despite compliance with biosafety measures that allow ensuring service quality standards, ensuring hygiene, order and safety at all times, the income received by users is restricted while the obligations that it maintains with financial institutions stand out for being pressing as well as threatening. The present research aims to contribute with ideas for the economic reactivation of the merchants in the markets of the city of Riobamba, specifically concentrating the case study of the La Condamine shopping center to try to revive the economy in the capital of the province of Chimborazo. The methodological framework is based on the quantitative approach, at the explanatory level, in the observational, documentary, retrospective and transversal types. The method was inductive when observing the reality in the Condamine market in order to be able to replicate it to the other markets. The results of the research identify the reality of the merchants and propose some strategies for economic reactivation during the emergency for the popular shopping center La Condamine.